Co-expression of VP2, NS1 and NS2-Nt proteins by an MVA viral vector induces complete protection against bluetongue virus - Jiménez-Cabello, Luis; Utrilla-Trigo, Sergio; Calvo-Pinilla, Eva; Lorenzo, Gema; Illescas-Amo, Miguel; Benavides, Julio; Moreno, Sandra; Marín-López, Alejandro; Nogales, Aitor; Ortego, Javier (Frontiers in Immunology, 2024)
Bluetongue (BT), caused by bluetongue virus (BTV), is an important arthropod-borne livestock disease listed by the World Organization for Animal Health. Live-attenuated and inactivated vaccines have permitted to control BT but they do not simultaneously protect against the myriad of BTV serotypes. Recently, we identified the highly conserved BTV nonstructural protein NS1 and the Nterminal region of NS2 as antigens capable of conferring multiserotype protection against BTV. Here, we designed Modified Vaccinia Ankara (MVA) viral vectors that expressed BTV-4 proteins VP2 or VP7 along with NS1 and NS2-Nt as well as MVAs that expressed proteins VP2, VP7 or NS1 and NS2-Nt. Immunization of IFNAR(-/-) mice with two doses of MVA-NS1-2A-NS2-Nt protected mice from BTV-4M infection by the induction of an antigen-specific T cell immune response. Despite rMVA expressing VP7 alone were not protective in the IFNAR(-/-) mouse model, inclusion of VP7 in the vaccine formulation amplified the cell-mediated response induced by NS1 and NS2-Nt. Expression of VP2 elicited protective non-cross-reactive neutralizing antibodies (nAbs) in immunized animals and improved the protection observed in the MVA-NS1-2A-NS2-Nt immunized mice when these three BTV antigens were co-expressed. Moreover, vaccines candidates coexpressing VP2 or VP7 along with NS1 and NS2-Nt provided multiserotype protection. We assessed protective efficacy of both vaccine candidates in sheep against virulent challenge with BTV-4M. Immunization with MVA-VP7-NS1-2A-NS2-Nt partially dumped viral replication and clinical disease whereas administration of MVA-VP2-NS1-2A-NS2-Nt promoted a complete protection, preventing viraemia and the pathology produced by BTV infection.